2006
DOI: 10.1021/jo060427+
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cycloaddition Reaction of [60]Fullerene with Carbonyl Ylides Generated from Epoxides

Abstract: The thermal reaction of [60]fullerene (C60) with the carbonyl ylides generated in situ from trans-epoxides to give C60-fused tetrahydrofuran derivatives has been investigated. The reaction of C60 with trans-2-benzoyl-3-aryloxiranes afforded only cis-products, while the reaction of C60 with 2-cyano-2-ethoxycarbonyl-3-aryloxiranes gave exclusively or predominantly cis isomers. The isomeric distributions of the latter reactions were drastically affected by the substituent on the phenyl ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…[35][36][37] The 1 HNMR spectrum of 3a also shows the extremely similar chemical shifts as that of the cisconformation adduct proposed using the NOESY spectrum ( Figure S11). [35][36][37] Therefore,t he molecular structure of 3a can be confirmed as cis-conformation. Meanwhile,t he 1 HNMR spectrum of 3b has the approximately same chemical shifts as that of the trans-conformation adduct reported by Yang et al, which is consistent with the crystal structure of 3b ( Figure S12).…”
Section: Angewandte Chemiesupporting
confidence: 53%
See 1 more Smart Citation
“…[35][36][37] The 1 HNMR spectrum of 3a also shows the extremely similar chemical shifts as that of the cisconformation adduct proposed using the NOESY spectrum ( Figure S11). [35][36][37] Therefore,t he molecular structure of 3a can be confirmed as cis-conformation. Meanwhile,t he 1 HNMR spectrum of 3b has the approximately same chemical shifts as that of the trans-conformation adduct reported by Yang et al, which is consistent with the crystal structure of 3b ( Figure S12).…”
Section: Angewandte Chemiesupporting
confidence: 53%
“…The1 ,3-dipolar cycloaddition of C 60 with carbonyl ylides formed via a,b-epoxy ketones is an effective approach for chemical functionalization of fullerenes. [35][36][37] However,t he a,b-epoxy ketones could generate three possible ylide intermediates with two trans-( exo,e ndo) and one cis-( exo,e xo) conformations by the conrotatory of CÀCb ond cleavage, resulting in the uncontrolled formation of both trans-and cisadducts. [38] Considering the considerable discrepancies on the electronic configurations between Sc 3 N@D 3h -C 78 and C 60 ,i n our present work we manage to explore such a1 ,3-dipolar cycloaddition of Sc 3 N@D 3h -C 78 with carbonyl ylide so as to investigate whether Sc 3 N@D 3h -C 78 exhibits the same addition regioselectivity and conformation selectivity as that of C 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Prow et al [11] have worked on nano-and micro-particles for skin drug delivery. Zhang et al [12] have experimentally showed the synthesis of C60 fullerene with the end-capped polystyrene, while Wang et al [13] have investigated the novel cycloaddition reaction of fullerene C60 with carbonyl ylides generated from epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…5 Aryl oxiranylcarboxylates/ketones undergo interesting C-C bond heterolysis of the oxirane ring, generating carbonyl ylides 6 that undergo dipolar cycloaddition with various π-systems. For example, the [3+2] cycloaddition of aryl oxiranyl-dicarboxylate/diketone/cyanoketone with indole, 7 alkyne, 8 or [60]fullerene 9 furnishes furo [3,4-b]indole, 2,5-dihydrofuran, or C60-fused tetrahydrofuran, respec-tively. Other significant applications of 2,3-epoxy esters/ketones include [3+2] heterocyclization for the construction of quaternary imidazole skeletons, 10 palladium(0)-catalyzed transformation into β-diketone, 11 and SmI 2 -mediated deoxygenation to produce the α,β-unsaturated ester.…”
mentioning
confidence: 99%